Penerapan Good Corporate Governance dan Earning Management terhadap Biaya Hutang pada Perusahaan BUMN Listing CGPI 2010 – 2012 - Rieke Pernamasari (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2018)
The company's efforts in increasing the high trust of creditors will be low risk, so the company can improve the effectiveness of motoring action that is in company like Good Corporate Governance. Investors tend to see the level of GCG implementation as an indicator of the company's risk level before making a funding decision. While the decision of investors in investing in a company based on various considerations, one of which is profit. As an organization, BUMN functioning as a development agent but also carrying out government policies and programs, while on the other hand it is required to become a healthy business unit. The results of this study indicate that the GCG index has no significant effect on the cost of debt and accrual income management has a significant effect on the cost of debt. It means that earnings management is done by management to influence investor perception, especially to influence buying decision of company stock and influence company value.